PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VII SMP NEGERI 41 PADANG - Bunga Maysuri, Ananda; Rasyid, Yulianti; Hafrison, Mohamad; Indriyani, Vivi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to describe the following aspects. First, to describe the planning of the implementation of the Project Based Learning (PjBL) model assisted by audiovisual media in teaching news text writing to seventh-grade students at SMP Negeri 41 Padang. Second, to describe the implementation of the Project Based Learning (PjBL) model assisted by audiovisual media in teaching news text writing to seventh-grade students at SMP Negeri 41 Padang. Third, to describe the evaluation of the implementation of the Project Based Learning (PjBL) model assisted by audiovisual media in teaching news text writing to seventh-grade students at SMP Negeri 41 Padang. This study employs three main theoretical frameworks. These theories are used to analyze and discuss the research findings. First, the theory of teaching news text writing skills. Second, the Project Based Learning (PjBL) model assisted by audiovisual media. Third, the implementation of the PjBL model. This research uses a qualitative approach with a descriptive method. The data in this study include teaching modules, the process of teaching news text writing, and student worksheets (LKPD). The data sources are the subjects from which the data are obtained, including teachers, students, and the teaching and learning process. The data collection techniques used in this study are observation and interviews. The results of this study show three main findings. First, well-prepared planning plays an important role in the successful implementation of the Project Based Learning (PjBL) model assisted by audiovisual media. Second, the implementation of the Project Based Learning (PjBL) model assisted by audiovisual media increases students’ engagement in learning to write news texts. Third, the evaluation indicates that the Project Based Learning (PjBL) model assisted by audiovisual media is more engaging compared to conventional methods. Therefore, it can be concluded that the implementation of the Project Based Learning (PjBL) model assisted by audiovisual media has been successfully applied in teaching news text writing to seventh-grade students at SMP Negeri 41 Padang.